2020
DOI: 10.1148/radiol.2020200823
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Radiologists in Differentiating COVID-19 from Non-COVID-19 Viral Pneumonia at Chest CT

Abstract: Key Results: Three Chinese radiologists had a sensitivity of 72%, 72% and 94% and specificity of 94%, 88% and 24% in differentiating 219 COVID-19 from 205 non-COVID-19 pneumonia.  Four United States radiologists had a sensitivity of 93%, 83%, 73% and 73% and specificity of 100%, 93%, 93% and 100%.  The most discriminating features for COVID-19 pneumonia included a peripheral distribution (80% vs. 57%, p<0.001), ground-glass opacity (91% vs. 68%, p<0.001) and vascular thickening (58% vs. 22%, p<0.001). Manus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
1,129
9
58

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,154 publications
(1,264 citation statements)
references
References 10 publications
68
1,129
9
58
Order By: Relevance
“…1-C). According to the published data to that date, the mentioned findings were not completely in concordance with COIVD-19 [3,[7][8][9]. However, due to the abnormal imaging findings, the patient was transferred to our center.…”
Section: Case Presentationmentioning
confidence: 82%
“…1-C). According to the published data to that date, the mentioned findings were not completely in concordance with COIVD-19 [3,[7][8][9]. However, due to the abnormal imaging findings, the patient was transferred to our center.…”
Section: Case Presentationmentioning
confidence: 82%
“…CT features largely overlap, even though it has been reported that CT abnormalities in COVID-19 pneumonia more frequently exhibit a peripheral predominance, with less frequent pleural effusion and lymphadenopathy ( Fig. 10) [19]. It is mainly the high current epidemic context which suggests COVID-19 as the cause of GGO in patients with fever and respiratory symptoms.…”
Section: Ct Features Suggesting Pneumonia Of Other Causementioning
confidence: 95%
“…This shows the limitation of imaging. However, where the differential diagnosis is between COVID-19 and non-COVID-19 viral pneumonia, radiologists from China and the United States have had high specificity but moderate sensitivity according the most recent research [26]. This suggests that a negative diagnosis of COVID-19 may exclude patients who in fact have COVID-19.…”
Section: Chest Ct Features Of Covid-19mentioning
confidence: 99%